2019
DOI: 10.1214/19-aoas1285
|View full text |Cite
|
Sign up to set email alerts
|

Outline analyses of the called strike zone in Major League Baseball

Abstract: We extend statistical shape analytic methods known as outline analysis for application to the strike zone, a central feature of the game of baseball. Although the strike zone is rigorously defined by Major League Baseball's official rules, umpires make mistakes in calling pitches as strikes (and balls) and may even adhere to a strike zone somewhat different than that prescribed by the rule book. Our methods yield inference on geometric attributes (centroid, dimensions, orientation and shape) of this "called st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We also observed that a research team with the same authors, well-versed in manipulating massive baseball data like PITCHf/x, published two studies in the same year. One applied a forward stepwise multiple regression model to investigate the pitching success, which is measured by fielding independent pitching (FIP), considering the relevance to pitch selection, ball speed, ball movement, release location, variation in pitch speed, variation in ball movement, and variation in release location (Zimmerman et al, 2019). The other examined the changes in pitching-performance characteristics across nine innings of MLB games using pitch type, speed, ball movement, release location, and strike-zone data to compare with the pitcher’s FIP (Guss et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that a research team with the same authors, well-versed in manipulating massive baseball data like PITCHf/x, published two studies in the same year. One applied a forward stepwise multiple regression model to investigate the pitching success, which is measured by fielding independent pitching (FIP), considering the relevance to pitch selection, ball speed, ball movement, release location, variation in pitch speed, variation in ball movement, and variation in release location (Zimmerman et al, 2019). The other examined the changes in pitching-performance characteristics across nine innings of MLB games using pitch type, speed, ball movement, release location, and strike-zone data to compare with the pitcher’s FIP (Guss et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of 10 papers were categorized as performance evaluations (Table 2), with eight of them using PITCHf/x data and three using massive pitch data over 1 million. The study with the largest amount of data is Zimmerman et al (2019), which uses more than 3 million called pitches from the 2008 to 2016 seasons to analysis the called strike zone (CSZ), to examine the performance of umpire. The second one is Mills (2017), which also studied the CSZ with 2.47 million pitch-level observations in the 2008 to 2014 regular seasons.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Deshpande and Evans (2020) use non-parametric Bayesian analysis and imputation methods to track how completion probability evolves through receivers' routes in the National Football League (NFL). In addition to player movement analyses, Zimmerman et al (2019) apply outline analysis to make inference on the geometric attributes of the called strike zone in Major League Baseball (MLB). Furthermore, a larger comparison of team strength within and competitiveness across sports leagues is estimated using Bayesian state-space modeling in Lopez et al (2018).…”
Section: Introductionmentioning
confidence: 99%